Rol' Meždunarodnych sportivnych igr «Deti Azii» v razvitii sporta v Respublike Sacha (Jakutija) - Olesov, N. P.; Chompodoeva, M. V.; Cerkašin, I. A.; Golikova, L. I. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The article analyzes the significance and role of international sports games "Children of Asia" in the development of sports in the Sakha Republic (Yakutia), the results of participants in the games in the sport of higher achievements. It has been established that for all the existence of the Games (from 1996 to 2016) the number of participating countries has increased 5.8 times, the regions of the Russian Federation - 1.8 times, participating athletes - 11.2 times, the number of Game species sports - in 2,7 times. More than 20 sports facilities have been built for the Games in the Republic. Many prize-winners of the Games become sportsmen of the highest qualification, prize-winners and winners of the Olympic Games and world championships. This shows that the International Sports Games "Children of Asia" make a significant contribution to the development of world children`s and youth sports, and their recognition in Russia and the world is constantly increasing.